ONLINE INTERNATIONAL HIGHER EDUCATION PROGRAMS: THE POSSIBILITIES OF A US AND UKRAINIAN PARTNERSHIP - Gardner, Г.А.; Baran, Г.П. (Journal of Information Technologies in Education (ITE), 2009)
This article examines the development of online courses as part of international programs and explores the use of online courses to overcome visa and other limitations in recruiting faculty and students to the United States. It specifically explores the possibility of joint-program partnerships between US and Ukrainian universities. It concludes that there are no major barriers to such partnerships that cannot be overcome through proper course design and adequate access to technology.